Math, asked by mdLovelu, 9 months ago

Prove (L.HS.=R.H.S)

(tanA+SinA) - (tanA-SinA)=2tanAcosA​

Answers

Answered by diksharana1784
2

please mark me as brainlist and also follow me...

Attachments:
Answered by krishnajha0706
1

Answer: PLZ MARK ME AS BRAINLIST

Step-by-step explanation:

LHS=(tanA+sinA)-(tanA-sinA)

       =(sinA/cosA+sinA)-(sinA/cosA-sinA)

       =(sinA+sinAcosA/cosA)-(sinA-sinAcosA/cosA)

       =sinA+sinAcosA-sinA+sinAcosA/cosA

      =2sinAcosA/cosA

      =2tanAcosA

Similar questions